2019
DOI: 10.1186/s12864-019-6037-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome changes reveal the genetic mechanisms of the reproductive plasticity of workers in lower termites

Abstract: Background The reproductive plasticity of termite workers provides colonies with tremendous flexibility to respond to environmental changes, which is the basis for evolutionary and ecological success. Although it is known that all colony members share the same genetic background and that differences in castes are caused by differences in gene expression, the pattern of the specific expression of genes involved in the differentiation of workers into reproductives remains unclear. In this study, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…In particular, the catalase activities of termite queens were higher than those of certain solitary insects and social Hymenoptera, reflected by an increased expression of the catalase gene RsCAT1 [46]. In addition, a study on another subterranean termite R. chinensis revealed that differentiation of workers into neotenic reproductives was associated with increased catalase gene expression [48]. These studies partially support the hypothesis that transition to a reproductive state is associated with a gradual decrease in the extent of oxidative damage to body tissues (the oxidative shielding hypothesis) [72].…”
Section: The Physiological and Molecular Mechanisms Of Extended Longevitymentioning
confidence: 98%
“…In particular, the catalase activities of termite queens were higher than those of certain solitary insects and social Hymenoptera, reflected by an increased expression of the catalase gene RsCAT1 [46]. In addition, a study on another subterranean termite R. chinensis revealed that differentiation of workers into neotenic reproductives was associated with increased catalase gene expression [48]. These studies partially support the hypothesis that transition to a reproductive state is associated with a gradual decrease in the extent of oxidative damage to body tissues (the oxidative shielding hypothesis) [72].…”
Section: The Physiological and Molecular Mechanisms Of Extended Longevitymentioning
confidence: 98%
“…Increased expression of antioxidant-encoding genes occurs in young queens and old workers, but not in old queens in Apis mellifera honeybees and Lasius niger ants [ 13 , 19 , 20 ], and the activity of antioxidant enzymes is not necessarily higher in long-lived castes [ 8 , 19 , 20 ]. In Reticulitermes termites, in which reproductives outlive workers and accumulate less damage to DNA, proteins, and lipids, catalase and peroxiredoxin gene expression is higher in queens, and so is catalase activity [ 16 , 21 ]. While the expression of superoxide dismutase genes does not differ between workers and reproductives, Sod activity is higher in reproductives [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 470- to 500-bp size ligation products were enriched to generate a strand-specific cDNA library for mRNA-seq. Construction of the mRNA libraries was performed as described earlier ( 20 ). A total of eight prepared cDNA libraries from two age groups were sequenced on Illumina HiSeq™ 4000 by Gene Denovo Biotechnology Co., Ltd. (Guangzhou, China).…”
Section: Methodsmentioning
confidence: 99%